INFLUENCE OF SOLAR RETROGRADE MOTION ON TERRESTRIAL PROCESSES - Sidorenkov, N. S.; Wilson, Ian (Одеські астрономічні публікації, 2017)
The influence of solar retrograde motion on secular minima of solar activity, volcanic eruptions, climate changes, and other terrestrial processes is investigated. Most collected data suggest that secular minima of solar activity, powerful volcanic eruptions, significant climate changes, and catastrophic earthquakes occur around events of solar retrograde motion.